2015
DOI: 10.1088/1742-6596/628/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Reinforced Concrete Slabs under Blast Loads of Close-in Detonations Using the Lagrangian Approach

Abstract: Comparison between a typical and a simplified model for blast load-induced structural response A Abd-Elhamed and S Mahmoud Abstract. This paper includes an investigation for the deformations, including deflections and damage modes, which occur in reinforced concrete (RC) slabs when subjected to blast loads of explosions. The slab considered for the investigation is a one-way square RC slab with the dimensions of 1000 x 1000 x 40 mm, fixed supported at two opposite sides. It was subjected to close-in detonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…The ConWep algorithm is an empirical formula for calculating explosive loads. By inputting parameters, such as the type, mass, initiation method, distance, and height of the explosive, various aspects of the explosive load can be calculated [ 31 ]. The pressure–impulse criterion is used to evaluate the blast loading, and it is found that the blast loading closely matches the pressure and impulse of the impact loading.…”
Section: Resultsmentioning
confidence: 99%
“…The ConWep algorithm is an empirical formula for calculating explosive loads. By inputting parameters, such as the type, mass, initiation method, distance, and height of the explosive, various aspects of the explosive load can be calculated [ 31 ]. The pressure–impulse criterion is used to evaluate the blast loading, and it is found that the blast loading closely matches the pressure and impulse of the impact loading.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the failed material act as a "load filter" for the remainder of the bar, which properties are determined by the EOS, the strength envelopes and the damage definition in the material models. Shuaib and Daoud demonstrated numerical modelling of reinforced concrete slabs under blast loads [95]. They selected KCC and Winfrith concrete models for concrete modelling.…”
Section: Numerical Examples and Comparison With Experimental Resultsmentioning
confidence: 99%
“…Smith và cs. [22,23]. Phương pháp CON-WEP còn được gọi là phương pháp Lagrangian thuần túy, trong đó tác động của vụ nổ được quy ra tải trọng đặt trực tiếp lên các bề mặt của kết cấu mà không thể hiện sự lan truyền sóng nổ.…”
Section: Tổng Quan Về Sóng Nổunclassified